Ethnic-specific mortality of infants undergoing congenital heart surgery in England and Wales. Issue 9 (1st March 2019) - Knowles, Rachel L; Ridout, Deborah; Crowe, Sonya; Bull, Catherine; Wray, Jo; Tregay, Jenifer; Franklin, Rodney C G; Barron, David J; Parslow, Roger C; Brown, Katherine
Abstract : Purpose: To investigate ethnic differences in mortality for infants with congenital heart defects (CHDs) undergoing cardiac surgery or interventional catheterisation. Design: Observational study of survival to age 1 year using linked records from routine national paediatric cardiac surgery and intensive care audits. Mortality risk was investigated using multivariable Poisson models with multiple imputation. Predictors included sex, ethnicity, preterm birth, deprivation, comorbidities, prenatal diagnosis, age and weight at surgery, preprocedure deterioration and cardiac diagnosis. Setting: All paediatric cardiac surgery centres in England and Wales. Patients: 5350 infants with CHDs born from 2006 to 2009. Main outcome measure: Survival at age 1 year. Results: Mortality was 83.9 (95% CI 76.3 to 92.1) per 1000 infants, with variation by ethnic group. Compared with those of white ethnicity, infants in British Asian (Indian, Pakistani and Bangladeshi) and 'all other' (Chinese, mixed and other) categories experienced significantly higher mortality by age 1 year (relative risk [RR] 1.52[95% CI 1.19 to 1.95]; 1.62[95% CI 1.20 to 2.20], respectively), specifically during index hospital admission (RR 1.55 [95% CI 1.07 to 2.26]; 1.64 [95% CI 1.05 to 2.57], respectively). Further predictors of mortality included non-cardiac comorbidities, prenatal diagnosis, older age at surgery, preprocedure deterioration and cardiac diagnosis. British Asian infants had higher mortality risk during elective hospital readmission (RR 1.86 [95% CI 1.02 to 3.39]). Conclusions: Infants of British Asian and 'all other' non-white ethnicity experienced higher postoperative mortality risk, which was only partly explained by socioeconomic deprivation and access to care. Further investigation of case-mix and timing of risk may provide important insights into potential mechanisms underlying ethnic disparities.